Induction of humoral immune response to multiple recombinant Rhipicephalus appendiculatus antigens and their effect on tick feeding success and pathogen transmission - Olds, Cassandra L.; Mwaura, S.; Odongo, David O.; Scoles, Glen A.; Bishop, Richard P.; Daubenberger, C.A. (Springer, 2016)
Background Rhipicephalus appendiculatus is the primary vector of Theileria parva, the etiological agent of East Coast fever (ECF), a devastating disease of cattle in sub-Saharan Africa. We hypothesized that a vaccine targeting tick proteins that are involved in attachment and feeding might affect feeding success and possibly reduce tick-borne transmission of T. parva. Here we report the evaluation of a multivalent vaccine cocktail of tick antigens for their ability to reduce R. appendiculatus feeding success and possibly reduce tick-transmission of T. parva in a natural host-tick-parasite challenge model. Methods Cattle were inoculated with a multivalent antigen cocktail containing recombinant tick protective antigen subolesin as well as two additional R. appendiculatus saliva antigens: the cement protein TRP64, and three different histamine binding proteins. The cocktail also contained the T. parva sporozoite antigen p67C. The effect of vaccination on the feeding success of nymphal and adult R. appendiculatus ticks was evaluated together with the effect on transmission of T. parva using a tick challenge model. Results To our knowledge, this is the first evaluation of the anti-tick effects of these antigens in the natural host-tick-parasite combination. In spite of evidence of strong immune responses to all of the antigens in the cocktail, vaccination with this combination of tick and parasite antigens did not appear to effect tick feeding success or reduce transmission of T. parva. Conclusion The results of this study highlight the importance of early evaluation of anti-tick vaccine candidates in biologically relevant challenge systems using the natural tick-host-parasite combination.